Charting a New Course : Structural Reforms in Colombia's Water Supply and Sanitation Sector - Andres, Luis A.; Sislen, David; Marin, Philippe (World Bank, Bogota, 2017)
Infrastructure plays a key role in promoting economic growth and opportunities.In particular, the efficient provision of basic infrastructure services, like water and sanitation, is a key ingredient in fostering a country's social and economic development. Previous studies have found that infrastructure has a positive impact on output, and can improve economic opportunity, including health and education for the poor, particularly in developing countries. In Argentina, a 2005 study, found that child mortality fell by 8 percent in areas that had experienced improved coverage and quality of basic water and sanitation through utility reform, with most of the reduction occurring in low-income areas where the water network expanded the most. More generally, Fay and Morrison found that allowing the poorest quintile in developing countries the same access to basic services as the richest quintile would reduce child mortality by 8 percent and child under development by 14 percent. Calderon and Serven also found a significant positive impact of infrastructure access and quality on overall inequality. Furthermore, the book sheds some light on how to address the main challenge for the future which may be to attract specialized operators to the smaller municipalities which do not currently have them. For that purpose in Colombia, for example, over the last two years, the policy framework has been focused on promoting the sector's development, by using the departments as the intermediate institutional level between the National Government and the municipalities, to formulate programs with regional impact and promote comprehensive investment plans.